Studying the Association of MTRR (rs1801394) Genetic Polymorphism with the risk of Developing Rheumatoid Arthritis in Uzbekistan - Marif Sh. Karimov; Aida A. Eshmurzayeva; Fazilat N. Shukurova; Marina V. Sibirkina; Asiya R. Gimadutdinova (Genius Journals, 2023)
We have studied the association of MTRR polymorphism (rs1801394) with the risk of developing rheumatoid arthritis among the population of Uzbekistan. The assessment of this genetic polymorphism was carried out by analyzing DNA samples by standard PCR. The results of the study we obtained made it possible to establish the correspondence between the differences between the expected and observed frequencies of the genotype variants of the MTRR (rs1801394) gene polymorphism for RHB (p>0.05) both in the group of patients and in the comparison group. The proportion of occurrence of unfavorable allele (G) and genotypes (A/G and G/G) in the general group of patients with RA and among patients with the articular form of the disease does not significantly differ from those in the control (χ2<3.84; Р>0.05). Only among patients with the articular-visceral form, there is a tendency to increase the occurrence of the A/G genotype by 1.6 times (χ2=1.3; P=0.262; OR=1.6; 95% CI: 0.716-3.504). Perhaps, with a larger coverage of the examined RA, a significant relationship with the development of the articular-visceral form of the disease could be established
Keywords: rheumatoid arthritis; MTRR genetic polymorphism; allele; frequency